2016
DOI: 10.1007/s00383-016-4009-8
|View full text |Cite
|
Sign up to set email alerts
|

Protocol-based management of 154 cases of pediatric liver abscess

Abstract: Ultra-sonography was useful for the initial diagnosis, monitoring the progress and management of LA in children. The outcome of a protocol-based management of LA in children was favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 24 publications
6
34
2
Order By: Relevance
“…However, a pediatric study in Taiwan and several adult studies have found that the spectrum of pathogenic bacteria has changed, and Klebsiella pneumoniae and Escherichia coli have gradually become the main pathogens. 2,5,6 The results of this study are similar to those in Taiwan. The possible reasons for this situation are that the incidence of Staphylococcus aureus is low in the author's area due to relatively good economic, medical and health conditions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, a pediatric study in Taiwan and several adult studies have found that the spectrum of pathogenic bacteria has changed, and Klebsiella pneumoniae and Escherichia coli have gradually become the main pathogens. 2,5,6 The results of this study are similar to those in Taiwan. The possible reasons for this situation are that the incidence of Staphylococcus aureus is low in the author's area due to relatively good economic, medical and health conditions.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, cryptogenic liver abscesses accounted for 52.6%, while a study of children in Taiwan showed that cryptogenic liver abscesses accounted for 70-80%. 5,6 Fever and abdominal pain are the most common symptoms. This study suggests that the right lobe of the liver is the most common site of bacterial liver abscesses, so right upper abdominal pain is more common, and some children have symptoms such as cough, shortness of breath and chest pain caused by the liver abscess stimulating the diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…Liver abscess is an important yet relatively uncommon disease in children, with varied incidence and prevalence worldwide (1). Liver abscess is uncommon in developed countries but remains a significant infectious issue for children residing in developing countries (2)(3)(4). The incidence rates reported in previous studies ranged from 25 per 100,000 pediatric admissions in the USA, 79 per 100,000 pediatric admissions in India, and up to 400 per 100,000 pediatric admissions in Cote d'Ivoire (3,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the treatment outcome has been improving gradually with higher clinical suspicion and rigorous treatment, although we still possess no consensual algorithm. The mortality rate due to liver abscess has dropped from 40% in the 1980s to below 15% (2,4,11).…”
Section: Introductionmentioning
confidence: 99%
“…However, the standard therapeutic management according to abscess size in PLA patients remains unclear [6,8,[14][15][16][17][18][19][20][21][22]. Kulhari and Mandia [19] suggested that percutaneous catheter drainage (PCD) is a better choice as compared to PNA especially in large abscesses that are partially liquefied.…”
Section: Introductionmentioning
confidence: 99%